Governance in Kazakhstan: improvements but could do better - Janenova, S.; Knox, C. (The Astana Times, 2018)
The World Bank Group has just published the latest governance indicators including how well Kazakhstan is performing. The picture over a 10-year period is a mixed bag. It shows that Kazakhstan has made significant improvements in government effectiveness which measures the quality of public services and improved capacity of the civil service. It also shows a marginal improvement in the control of corruption although progress is very limited given the time period involved. Finally, the latest figures show that voice and accountability, which measures freedom of expression, freedom of association, and a free media has become marginally worse over the decade...
Keywords: Kazakhstan; Governance in Kazakhstan